Sorbent for separation of gas streams
By exchanging the blend of lithium-exchange zeolite and low silica X zeolite and Eloite clay, combined with caustic digestion method, the problem of insufficient pore structure and mechanical strength of the adsorbent is solved, and efficient oxygen separation and prolonging the adsorbent life is achieved. .
Patent Information
- Application Number
- CN202380043277.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-20
- Filing Date
- 2023-06-19
- Publication Date
- 2025-01-10
AI Technical Summary
In the prior art, adsorbents for gas separation have shortcomings in pore structure and mechanical strength, resulting in problems with adsorption efficiency and life, especially in the absence of adhesive, where the manufacturing steps are complex and costly.
The blend of lithium exchange zeolite 13X, lithium exchange low silica X zeolite and Eloite clay is used as adsorbents. The Eloite clay is converted into zeolite 13X through caustic digestion to form an efficient adhesive-free adsorbent , optimize its pore structure and mechanical properties.
High capacity, fast kinetics and good pore structure characteristics are achieved, the bulk density, crushing strength and pore diffusion coefficient of the adsorbent are improved, and the oxygen separation efficiency and service life of the adsorbent are significantly improved.
Smart Images

Figure BDA0005156015850000041 
Figure BDA0005156015850000091
Abstract
Description
background Technical Field
[0001] The present invention is a zeolite adsorbent particularly useful for separation of gas streams. The adsorbent has surprising physical properties such as high tapped bulk density and crush strength, and further preferably exhibits high capacity, fast kinetics, excellent porosity and significant pore structure improvements relative to the prior art.
[0002] In one embodiment, it is suitable to separate and concentrate oxygen by adsorption from a mixed gas stream, such as a gas stream consisting primarily of nitrogen and oxygen.
[0003] The present invention also includes a gas separation process using the adsorbent. These gas separation processes include, for example, but not limited to, pressure swing adsorption (PSA), vacuum pressure swing adsorption (VPSA) and temperature swing adsorption (TSA). These processes are particularly useful for the separation and recovery of gases such as oxygen, nitrogen, carbon dioxide, hydrogen and other gaseous materials. Among these gases, oxygen is important for medical purposes. The production of oxygen by the PSA / VPSA process includes the selective adsorption of nitrogen from air onto the adsorbent, the extraction of the remaining concentrated oxygen and its collection as the final product.
[0004] The present invention is also a method for making and producing zeolite adsorbents useful for gas separations, particularly separation of oxygen from gas streams. Background Art
[0005] The adsorbents of the present invention are particularly useful for the adsorption and separation of gases. In one embodiment, the adsorbent composition is used to separate gases from a gas by subjecting the gas to a stream containing N 2 , O 2 and other air mixture is contacted with an adsorbent composition to separate O from the mixture. 2 The method wherein the adsorbent composition selectively adsorbs N 2 , one or more of the less strongly adsorbed components are collected as products.
[0006] Of particular interest is the use of these adsorbents in the production of O 2The use of adsorbents in non-cryogenic gas separation processes. For example, the separation of nitrogen from gas mixtures is the basis of several industrial adsorption processes, including the production of oxygen from air. In the production of oxygen from air cycles, air is passed through an adsorbent bed that has a tendency to adsorb nitrogen molecules and produce oxygen and argon (less strongly adsorbed components). The adsorbed nitrogen is then desorbed by a purge step, and the adsorbent is typically regenerated by a change in pressure (including vacuum) and / or by a change in temperature, and the cycle is repeated. Such processes include pressure swing adsorption (PSA), temperature swing adsorption (TSA), vacuum swing adsorption (VSA), and vacuum pressure swing adsorption (VPSA) processes. Such processes are commonly used in commercial air separation operations, as well as in other industrial and medical processes.
[0007] The adsorbent used in these methods is an important factor in achieving efficient, effective and competitive processes. The performance of the adsorbent depends on several factors, including the 2 The adsorption capacity, selectivity between gases, which will affect the production yield, and adsorption kinetics, which will optimize the number of adsorption cycles to improve the productivity of the process. The bulk density / crush strength / loss rate of the agglomerated particles are also very important, especially with respect to achieving satisfactory adsorbent life in adsorption methods and systems. Improvements in pore structure (as represented by median pore size, percentage of small pores, and pore connectivity characteristics) are also important in the performance of the adsorbent. A particularly important parameter in evaluating pore structure is hysteresis, which is a useful factor in evaluating pore connectivity. Another important parameter useful for evaluating the adsorption rate of an adsorbent is the pore diffusion coefficient (D p ), which is a measure of the adsorption rate. These factors generally depend on the particle pore structure and the overall pore structure and the definition of each factor is well known to those skilled in the art.
[0008] Conventional agglomerated adsorbents for such adsorption methods are composed of zeolite powder (microcrystalline particles) including ion exchange zeolite powder, depending on method and adhesive. Adhesive is to ensure the bonding of agglomerated particles that are usually in the form of beads, pellets and extrudates. Adhesive does not have adsorption properties usually, and their only function is to give agglomerated particles enough mechanical strength to withstand the harshness and adsorption process configured in the packed bed adsorption system, such as the vibration and stress they undergo during pressurization and decompression. The adhesive selected and its concentration also affect the final pore structure of agglomerated particles and the property of adsorbent. Known adhesive concentration should be as low as possible to reduce the mass transfer resistance that can be negatively affected by the excessive adhesive present in the hole. The lower concentration of adhesive can also increase the overall adsorption capacity of adsorbent. Some adhesives, temporary adhesives and other processing aids can also fill or otherwise partially block the particle holes, and other adhesives can have a negative impact on the final pore structure, which depends on the carrier solvent of the adhesive.
[0009] A common method for obtaining agglomerated adsorbent particles having low binder concentrations, improved pore structure, and low mass transfer resistance is to use a caustic digestion process to prepare what are known in the industry as "binderless adsorbents." These binderless adsorbents represent a way to obtain low binder contents (preferably less than about 5% by weight), but at the expense of additional manufacturing steps and higher costs. The conventional approach to caustic digestion is to employ a clay binder that can be converted to an active adsorbent zeolite material via a caustic digestion treatment. Several prior publications have claimed novel pore structures and have demonstrated various levels of improvement in adsorption rate properties resulting from the use of these binderless adsorbents.
[0010] Therefore, it is desirable to provide binderless adsorbents, methods of producing the adsorbents, and methods of separating oxygen from mixed air environments by processes such as pressure swing adsorption, temperature swing adsorption, vacuum swing adsorption, and vacuum pressure swing adsorption. Desirable features and characteristics of the present invention will become apparent from the subsequent detailed description and the appended claims, taken in conjunction with the accompanying examples and background of the invention. Summary of the invention
[0011] The present invention includes an adsorbent for separation of a gas stream, the adsorbent comprising a blend of lithium-exchanged zeolite 13X ("Li13X"), lithium-exchanged low silica X zeolite ("LiLSX"), and remaining halloysite clay. The amount of Li13X is about 5 to about 20% by weight of the adsorbent. The amount of LiLSX is about 80% to about 90% by weight of the adsorbent. The amount of halloysite clay is preferably about 0.1% to about 5.0% by weight of the adsorbent. Preferably, the adsorbent comprises at least 98%, particularly 99%, of the blend of the above-mentioned Li13X, LiLSX, and remaining halloysite clay. For the purposes of the present disclosure, all ratios and percentages are by weight.
[0012] The binderless adsorbent preferably exhibits a high capacity for adsorbing gas, fast kinetics as measured by kinetic testing, and good pore structure characteristics, while also preferably exhibiting a high crush strength. The binderless adsorbent also exhibits a high bulk density equal to or greater than about 640 g / L as measured in accordance with DIN / ISO 787.
[0013] The adsorbent also preferably exhibits a high hysteresis factor of at least about 0.6, indicative of pore connectivity, as measured by standard Hg porosimetry data, such as described in U.S. Pat. No. 9,486,732 B2. The hysteresis factor "R" is defined by the standard Hg porosimetry data, as shown in Equation 1, where: I(60000 psia) is the cumulative invasion volume at 60000 psia on the invasion curve, I(50 psia) is the cumulative invasion volume at 50 psia on the invasion curve, and E(50 psia) is the cumulative invasion volume at 50 psia on the extrusion curve.
[0014]
[0015] The adsorbent also preferably exhibits a relative humidity of at least about 5.0×10 -6 m 2 / s for nitrogen pore diffusion coefficient (Dp), as in and disclosed in, for example, U.S. Pat. No. 6,500,234 B2, U.S. Pat. No. 6,790,260 B2, and U.S. Pat. No. 9,486,732 B2.
[0016] The adsorbent also preferably has a modified pore structure having a median pore size of at least about 5 microns and a proportion of pores less than or equal to 0.1 microns of less than about 6.0%.
[0017] The present invention also includes a method for preparing an adsorbent for separation of a gas stream using the following steps:
[0018] Provide low silica X zeolite,
[0019] mixing the low silica X zeolite with halloysite clay to form a mixture, wherein the halloysite clay comprises from about 5% to about 20% by weight of the mixture;
[0020] forming a shaped product from the mixture;
[0021] calcining the shaped product;
[0022] caustic digesting the shaped product to convert at least about 70% by weight of the halloysite clay to zeolite 13X; and
[0023] The zeolite component in the shaped product is lithium exchanged to produce an adsorbent, wherein the adsorbent has a bulk density of at least about 640 g / L as measured in accordance with DIN / ISO 787, preferably has a hysteresis factor greater than or equal to 0.6 as measured by Hg porosimetry as described, for example, in U.S. Pat. No. 9,486,732 B2, and preferably exhibits a relative humidity of greater than or equal to 5.0×10 -6 m2 / s for the high pore diffusion coefficient of nitrogen (D p ).
[0024] The invention also includes a method of using the adsorbent to separate gaseous materials, particularly oxygen from a gas stream. DETAILED DESCRIPTION
[0025] Disclosed is a method for separating gas streams, in particular O from air, by pressure swing adsorption (PSA), vapor pressure swing adsorption (VPSA) or temperature swing adsorption (TSA). 2 Particularly useful adsorbents for
[0026] One adsorbent particularly useful for the process consists of X or Y zeolite crystals, particularly X zeolite. Preferred are one or more types of zeolite X incorporating cations such as Li, Ca, K, Na, Ag and mixtures thereof, particularly Li, with one embodiment being a zeolite X containing Li cations. SiO 2 / Al 2 O 3 The ratio is preferably less than 15, in one embodiment less than 5, and in another embodiment less than or equal to 2.5. Particularly alternative embodiments have a SiO ratio of about 1.9 to about 2.3. 2 / Al 2 O 3 (For purposes of this disclosure, zeolite X having a silica to alumina ratio of less than or equal to 2.3 is referred to as a "low silica X zeolite," "LSX zeolite," or "LSX." Zeolite X having a silica to alumina ratio of greater than 2.3 to about 2.6 is referred to as a "13X zeolite," "zeolite 13X," or "13X." For purposes of this disclosure, lithium-exchanged 13X zeolite is referred to as a "lithium-exchanged zeolite 13X," "Li13X," or "Li13X zeolite," and lithium-exchanged low silica zeolite X is referred to as a "lithium-exchanged low silica X zeolite," "LiLSX," "LiX," or "zeolite LiX.")
[0027] A limitation on the use of zeolite crystals is their extremely fine particle size. Naturally formed agglomerates of these crystals break easily. Because the pressure drop across a bed of these zeolite crystals is too high, they cannot usually be used alone in a fixed bed in many applications.
[0028] It is therefore useful to agglomerate these crystals with a binder material to provide an agglomerated mass that exhibits a reduced pressure drop.
[0029] Various clay materials, such as kaolin or attapulgite clay, are commonly used as binder materials for these zeolite crystals. In addition, silicone-derived binders are used, such as those disclosed in US Pat. No. 9,486,732 B2 and US Pat. No. 9,050,582 B2.
[0030] While such binder materials are useful, it has been found that the use of binders in these agglomeration materials reduces the overall effectiveness of the zeolite product in the adsorption process.
[0031] In order to overcome this problem, so-called "binderless adsorbent" materials have been produced in which the clay binder material is at least substantially converted to a zeolite.
[0032] In order to produce the binderless material, it is necessary to convert at least substantially all of the binder into a useful zeolite blend material.Because kaolin clay can be converted into a low silica LiX zeolitic material using a caustic digestion process, prior art binderless LiX adsorbents have typically used kaolin as a binder for forming the binderless adsorbent.
[0033] It has surprisingly been found that halloysite clay can produce improved properties in adsorbents when used as a binder material for low silica LiX zeolites.In a preferred embodiment, the halloysite clay has a tubular shape with a length of about 0.5-2.0 microns and a diameter of about 50-100 nm.
[0034] In one embodiment, the method of making an agglomerated binderless sorbent composition is as follows:
[0035] a. preparing a mixture containing one or more active zeolite materials and a halloysite clay binder,
[0036] b. mixing the zeolite material and the halloysite clay material with water and forming agglomerated adsorbent particles,
[0037] c. drying the agglomerated adsorbent particles,
[0038] d. calcining the dried agglomerated sorbent particles to form calcined sorbent particles,
[0039] e. caustic treating the calcined sorbent particles to convert at least a portion of the halloysite clay binder to 13X zeolite;
[0040] f. treating the calcined sorbent particles with a metal salt solution to ion exchange at least a portion of the cations present into ion-exchanged agglomerated sorbent particles, and
[0041] g. Drying and activating the ion-exchanged agglomerated particles by heating the ion-exchanged agglomerated particles to form an agglomerated sorbent composition.
[0042] In one method of producing a binderless adsorbent, LSX zeolite is provided in an amount of about 80% to about 95% by weight of the total blend of materials. The LSX zeolite is mixed with halloysite clay in an amount of about 5% to about 20% by weight of the total blend, and the mixed components are kneaded together to form a uniform blended product. Water is preferably used during the formation of the blended product. The amount of water added and other characteristics of the mixing step depend on the amount of materials used therein.
[0043] The blended product is kneaded, granulated and shaped into a preferred shaped product. It can be shaped into beads, extrudates and / or spray-dried microspheres and in one embodiment, it can be shaped into beads.
[0044] The resulting product is then dried at a temperature of about 100° C. to 400° C. After drying it is calcined at a temperature of about 500 to about 700° C. to produce a shaped LSX / halloysite clay blend product.
[0045] The LSX / halloysite clay blend product is then treated with a caustic solution which converts a significant portion of the halloysite clay to zeolite 13X. In one embodiment, about 60% to about 95% or more of the halloysite clay by weight is converted to zeolite 13X. The process of caustic digestion of the halloysite clay material with a caustic solution occurs at a temperature of about 80°C. In one embodiment the caustic solution comprises primarily sodium hydroxide and potassium hydroxide. In other embodiments the caustic solution is essentially sodium hydroxide. The use of large amounts of sodium hydroxide for caustic treatment results in substantially more zeolite 13X being produced from the halloysite clay. Other combinations of hydroxides and other materials may be used to modify the final composition of the adsorbent.
[0046] There is no limitation on the exact method of contacting the blended product with the caustic solution.In one method the blended product is charged into a fixed bed column and the caustic solution is circulated throughout the bed column.
[0047] After the conversion process, the product is exchanged with lithium by at least about 90%, in one embodiment at least about 95%, and in another embodiment at least about 98%, to produce a final adsorbent. The final adsorbent contains about 80% to about 90% by weight LiLSX and about 5% to about 20% by weight Li13X, with the remainder being residual halloysite clay in an amount of about 0.1% to about 5% by weight. Also present in the final composition of the adsorbent after conversion may be any oxide of the following elements, alone or in combination: Al, Si, Ba, Li, Na, K, Mg, Ca, Fe, Ti, Y and Zr, as well as other residual components.
[0048] Preferred adsorbents in the prior art preferably use kaolin clay as a binder and, when the kaolin clay is converted to a zeolite, have the same composition as the primary zeolite used for the desired adsorption process. For example, caustic digestion of kaolin clay typically produces a low silica LiX zeolite. Applicants have discovered that surprisingly useful adsorbents containing both LiLSX zeolite and Li13X zeolite with a certain amount of residual halloysite clay can be produced.
[0049] The adsorbent produced by this method has enhanced physical properties compared to prior art adsorbents.
[0050] In one embodiment the adsorbent exhibits a tapped bulk density of at least about 640 g / L and a crush strength of at least about 8 N / mm as measured according to DIN / ISO 787.
[0051] Despite these physical properties, the adsorbent also surprisingly and preferably exhibits a good pore structure as measured by median pore size, a low proportion of pores less than or equal to 0.1 microns, and a high hysteresis factor (indicative of pore connectivity). The median pore size is preferably greater than or equal to 5 microns in one embodiment and the proportion of pores less than or equal to 0.1 microns is preferably less than about 10%, and in one embodiment preferably less than about 6%. The adsorbent also surprisingly and preferably exhibits a hysteresis factor greater than or equal to about 0.6 when measured by standard Hg porosimetry data, such as described in U.S. Pat. No. 9,486,732 B2.
[0052] Typically, materials with high density and high crush strength exhibit low porosity and potentially slower nitrogen absorption rates. Surprisingly, the disclosed adsorbent compositions have high strength and high crush strength and low porosity and have surprisingly fast nitrogen absorption rates attributable to the characteristics of the pore structure.
[0053] Due to these characteristics of the disclosed adsorbent composition, it preferably exhibits a thermal conductivity greater than 5.0×10 -6 m 2 / s for nitrogen pore diffusion coefficient (D p ) is used to measure the high adsorption rate. For nitrogen, the pore diffusion coefficient (D p The high value of ) indicates that the diffusion of material within the particle is surprisingly fast. p ) is surprising, especially considering the physical properties of the adsorbent particles. p ) is determined based on the nitrogen pore diffusion coefficient when measured at 1.5 bar and 300 K as described in, for example, U.S. Pat. No. 6,500,234 B2, U.S. Pat. No. 6,790,260 B2, and U.S. Pat. No. 9,486,732 B2.
[0054] Example
[0055] Invention Example 1
[0056] Low silica zeolite X (silica / alumina ratio of 2.0) was mixed with halloysite clay in a ratio of about 85 / 15 zeolite to clay by weight. The mixture was then formed into spheres and calcined. The calcined particles were then introduced into a hot (~90°C) sodium hydroxide solution for several hours to convert the clay to 13X zeolite. The particles were then washed with water to remove excess caustic and then the particles were subjected to lithium ion exchange to at least about 95%. The amount of lithium exchanged low silica zeolite X was 85%, the amount of lithium exchanged zeolite 13X was 12%, and the amount of residual halloysite clay was 3%.
[0057] Comparative sample 1 (C-1)
[0058] A shaped adsorbent comprising a lithium exchanged low silica X zeolite with an attapulgite binder as described in columns 3-8 of US Patent No. 7,300,899.
[0059] Comparative sample 2 (C-2)
[0060] Binderless adsorbents as described in columns 8 and 9 of US Pat. No. 6,425,940 Bl.
[0061] Comparative sample 3 (C-3)
[0062] A shaped adsorbent containing a lithium exchanged low silica X zeolite and a silica based binder as described in Example 2 of US Patent No. 9,486,732 B2.
[0063] Comparative sample 4 (C-4)
[0064] A binderless shaped adsorbent containing LiLSX available from Tosoh having the trade name NSA-700.
[0065] Comparative sample 5 (C-5)
[0066] Binder-free shaped sorbent containing LiLSX available from Hanchang.
[0067] In the following Table 1, the properties of Inventive Example 1 are compared with the adsorbents of Comparative Samples C-1, C-2, C-3, C-4 and C-5.
[0068] Table 1
[0069]
[0070] 1 Micrometer
[0071] 2 g / L
[0072] 3 N / mm
[0073] 4 See the description of the pore hysteresis factor in U.S. Pat. No. 9,486,732 B2
[0074] 5 The pore diffusion coefficient (D) for nitrogen described in U.S. Pat. No. 6,500,234 B2 and U.S. Pat. No. 6,790,260 B2 p ).
[0075] 6 Pores smaller than 0.1 micrometer as analyzed by mercury porosimetry.
[0076] From the data in Table 1, it is apparent that the inventive adsorbent compositions containing a combination of LiX and Li13X with residual halloysite clay have an optimal combination of both physical properties and pore structure, including median pore size, a low percentage of pores less than 0.1 μm, an improved hysteresis factor, and a higher diffusion coefficient for nitrogen. Despite these improved properties, the inventive compositions also have a higher tapped bulk density and a higher crush strength than the comparative examples.
[0077] Although conventional compositions with high density and crush strength traditionally imply reduced mass transfer or pore diffusion coefficients (D p ) composition, but surprisingly, the inventive composition exhibited a higher pore diffusion coefficient (D) for nitrogen than the comparative composition. p ). Despite the high density and crush strength of the composition, the inventive composition also exhibits a surprisingly fast diffusion rate within the particles. The nitrogen absorption rate of the inventive composition is also surprisingly fast compared to other compositions.
[0078] The binderless adsorbents of the present invention are particularly useful for separation of gas streams, for example for recovery of concentrated oxygen by selective adsorption of nitrogen from air. When using a PSA, VPSA or TSA process to concentrate oxygen from air, the operation comprises a series of steps, including an adsorption step, in which a packed bed of binderless zeolite material is contacted with air to selectively adsorb nitrogen. The concentrated oxygen is then collected from the outlet of the packed bed. Further processing of the gaseous material is conventional.
[0079] The adsorbent of the present invention is particularly effective for air separation by the PSA / VPSA / TSA process. When air is separated by the PSA / VPSA / TSA process, the amount and yield of concentrated oxygen are high and the adsorbent exhibits good physical properties and a long service life.
[0080] The foregoing detailed description is provided for understanding and does not provide any limitation on the scope of the claims. Modifications to the present invention will be apparent to those skilled in the art after reviewing this disclosure without departing from the scope of the claims.
Claims
1. An adsorbent for separation of a gas stream, comprising A blend of lithium exchanged zeolite 13X (Li13X), lithium exchanged low silica X zeolite (LiLSX) and halloysite clay, wherein Li13X accounts for about 5 to about 20% by weight of the adsorbent, wherein LiLSX comprises 80 to about 90% by weight of the adsorbent, and wherein the halloysite clay comprises about 0.1% to 5.0% by weight of the adsorbent, and The adsorbent has a bulk density of at least about 640 g / L, measured according to DIN / ISO 787.
2. The adsorbent according to claim 1, wherein the adsorbent exhibits a relative humidity greater than 5.0×10 -6 m 2 The pore diffusion coefficient (Dp) for nitrogen described in U.S. Pat. No. 6,500,234 B2 and U.S. Pat. No. 6,790,260 B2 is 0.0447 W / s.
3. The adsorbent according to claim 1 or 2, wherein the adsorbent exhibits a median pore size greater than or equal to 5 microns and a percentage of pores smaller than 0.1 microns less than 6.0%.
4. The adsorbent according to any one of claims 1 to 3, wherein the adsorbent exhibits a crush strength greater than 8 N / mm.
5. The adsorbent of any one of claims 1-4, wherein the adsorbent exhibits a hysteresis factor of at least about 0.6 as measured by Hg porosimetry as described in U.S. Pat. No. 9,486,732 B2.
6. A method for preparing an adsorbent for separation of a gas stream, comprising the steps of: Provide low silica X zeolite; mixing the zeolite with halloysite clay to form a mixture, wherein the halloysite clay comprises from about 5% to about 20% by weight of the mixture; forming a shaped product from the mixture; calcining the shaped product; caustic treating the calcined shaped product to convert at least a portion of the halloysite clay to 13X zeolite; and lithium exchanging LSX and 13X zeolites of the shaped product to produce the adsorbent; wherein the adsorbent comprises from about 0.1 to about 0.5% by weight of halloysite clay; and The adsorbent has a bulk density of at least about 640 g / L, measured according to DIN / ISO 787.
7. The method of claim 6, wherein the halloysite clay has a tubular shape having a length of about 0.5-2.0 microns and a diameter of about 50-100 nm.
8. A method according to claim 6 or 7, wherein the shaped product is caustic treated with a hydroxide substantially comprising sodium hydroxide.
9. The method according to any one of claims 6 to 8, wherein the adsorbent exhibits a relative humidity greater than 5.0×10 -6 m 2 The pore diffusion coefficient (Dp) for nitrogen described in U.S. Patent Nos. 6,500,234 B2 and 6,790,260 is 0.0447 W / s.
10. The method according to any one of claims 6 to 9, wherein the adsorbent exhibits a median pore size greater than or equal to 5 microns and a percentage of pores smaller than 0.1 microns less than 6%.
11. The method according to any one of claims 6 to 10, wherein the adsorbent exhibits a crush strength greater than 8 N / mm.
12. The method of any one of claims 6-11, wherein the adsorbent exhibits a hysteresis factor of at least about 0.6 as measured by Hg porosimetry as described in U.S. Pat. No. 9,486,732 B2.
13. A method for producing concentrated oxygen from a gas stream using the adsorbent according to claim 1.
Citation Information
Patent Citations
Advanced adsorbent for PSA
US6425940B1
Rate-enhanced gas separation
US6500234B1
Enhanced rate PSA process
US6790260B2
Lithium exchanged zeolite X adsorbent blends
US7300899B2
Adsorbent compositions
US9050582B2